Quality of Life in Older Adults After Major Cancer Surgery: The GOSAFE International Study. (8th April 2022) - Montroni, Isacco; Ugolini, Giampaolo; Saur, Nicole M; Rostoft, Siri; Spinelli, Antonino; Van Leeuwen, Barbara L; De Liguori Carino, Nicola; Ghignone, Federico; Jaklitsch, Michael T; Somasundar, Ponnandai; Garutti, Anna; Zingaretti, Chiara; et al.
Abstract: Background: Accurate quality of life (QoL) data and functional results after cancer surgery are lacking for older patients. The international, multicenter Geriatric Oncology Surgical Assessment and Functional rEcovery after Surgery (GOSAFE) Study compares QoL before and after surgery and identifies predictors of decline in QoL. Methods: GOSAFE prospectively collected data before and after major elective cancer surgery on older adults (≥70 years). Frailty assessment was performed and postoperative outcomes recorded (30, 90, and 180 days postoperatively) together with QoL data by means of the three-level version of the EuroQol five-dimensional questionnaire (EQ-5D-3L), including 2 components: an index (range = 0-1) generated by 5 domains (mobility, self-care, ability to perform the usual activities, pain or discomfort, anxiety or depression) and a visual analog scale. Results: Data from 26 centers were collected (February 2017-March 2019). Complete data were available for 942/1005 consecutive patients (94.0%): 492 male (52.2%), median age 78 years (range = 70-95 years), and primary tumor was colorectal in 67.8%. A total 61.2% of all surgeries were via a minimally invasive approach. The 30-, 90-, and 180-day mortality was 3.7%, 6.3%, and 9%, respectively. At 30 and 180 days, postoperative morbidity was 39.2% and 52.4%, respectively, and Clavien-Dindo III-IV complications were 13.5% and 18.7%, respectively. The mean EQ-5D-3L index was similar before vs 3 months but improved at 6 months (0.79 vs 0.82; P < .001). Domains showing improvement were pain and anxiety or depression. A Flemish Triage Risk Screening Tool score greater than or equal to 2 (odds ratio [OR] = 1.58, 95% confidence interval [CI] = 1.13 to 2.21, P = .007), palliative surgery (OR = 2.14, 95% CI = 1.01 to 4.52, P = .046), postoperative complications (OR = 1.95, 95% CI = 1.19 to 3.18, P = .007) correlated with worsening QoL. Conclusions: GOSAFE shows that older adults' preoperative QoL is preserved 3 months after cancer surgery, independent of their age. Frailty screening tools, patient-reported outcomes, and goals-of-care discussions can guide decisions to pursue surgery and direct patients' expectations.